Simulation of Flood Event in Kelantan on December 2014 as revealed by the HEC-HMS - Muhamad Zulhilmi Abdul Latif (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
A devastating flood disaster occurred at Kuala Krai, Kelantan on December 2014. The flood disaster had given a significant destructive impact on the infrastructure and as a result, almost 1,600 homes were lost or destroyed. This extreme flood event killed 25 villages and forced 45,467 people in Kuala Krai, Kelantan to be evacuated from their homes. Continuous heavy rain for over three days from the 21st to the 23rd of December, 2014 was set a rainfall record of 1,295 mm, equivalent to the amount of rain usually seen in a span of 64 days. As a result, the water levels of three major rivers, the Sungai Galas in Dabong, the Sungai Lebir in Tualang and the Sungai Kelantan in Jambatan Gueillemard, rose above the dangerous water levels. It is essential to estimate the extent of flood inundation. The objective of this study is to simulate flood event in December 2014 by using HEC-HMS. The results show the peak discharges and inundations occurred approximately on the 25th December 2014; 18,575.7 m3/s to be almost similar magnitude as reported by DID 2014 Flood Report. These findings led to the conclusion that the HEC-HMS model is useful as a flood analysis tool.